Life in occupied Palestine [videorecording (DVD)] : eyewitness stories & photos - Baltzer, Anna, 1979-; Pan, Chun; Rovics, David (Www.AnnaInTheMiddleEast.com, 2007)
Provides critical information and documentation on the Israel/Palestine conflict, and encourages dialogue towards taking nonviolent action on the issue.